THE ROLE OF COST ACCOUNTING IN THE DETERMINATION OF SELLING PRICES - Wilda Sri Munawaroh Harahap (CV. Barokah Publsiher, 2025)
This study aims to analyze the role of cost accounting in determining the selling price of a product. The study was conducted using a qualitative method of literature study approach to 12 scientific articles published in the last five years. The results show that cost accounting, especially the full costing and cost plus pricing methods are very important to ensure the right selling price in order to cover all production costs and provide optimal profit. In manufacturing companies, accurate cost calculations are needed for the entire length of overhead costs, while in MSMEs, the application of cost accounting can minimize losses due to inappropriate prices. Thus, cost accounting plays an important role in making decisions on selling price determination strategies so that business desires can be maintained.